Observation of Fine Structures of Defective Herbal Acupuncture Needles - Won Pil Park; Hyundo Kim; Ki Rok Kwon (Korean Pharmacopuncture Institute, 2005)
Objectives : This study was conducted to observe the tip of needles which induce poor needle sensation upon injection of herbal acupuncture. Methods : Among the syringes used for herbal acupuncture, needles which cause poor sensation were collected and evaluated by SEM (scanning electron microscope) for changes in structure, existence of impure matters, physical damage, and etc. Results : 1. Various forms contributed to poor needle sensation. Bent needle body, damaged or crooked needle tip, and blunted tip. 2. Poor needles could be made during the manufacturing process, during insertion of the needle into the vial (except for the lubricants), and repeated procedures with one needle at different regions. Conclusion : Poor needles induce unnecessary pain and discomfort not only to the patients but also to administrators during injection. Herbal acupuncture is a treatment technique injecting herbal extract on the meridian points, and strict quality check must be enforced to prevent occurrence of poor needles.